2013
DOI: 10.13001/1081-3810.1695
|View full text |Cite
|
Sign up to set email alerts
|

Maxima of the Q-index, Forbidden 4-ycle and 5-cycle

Abstract: Abstract. This paper gives tight upper bounds on the largest eigenvalue q (G) of the signless Laplacian of graphs with no 4-cycle and no 5-cycle.If n is odd, let Fn be the friendship graph of order n; if n is even, let Fn be F n−1 with an extra edge hung to its center. It is shown that if G is a graph of order n ≥ 4, with no 4-cycle, thenLet S n,k be the join of a complete graph of order k and an independent set of order n − k. It is shown that if G is a graph of order n ≥ 6, with no 5-cycle, thenIt is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Now, suppose that G has no isolated vertices. Select a vertex u with x u = 0 and let {u, v} ∈ E. Then we have strict inequality in (14) and so A α (G) is positive definite. ✷…”
Section: Positive Semidefinitness Of a Amentioning
confidence: 99%
“…Now, suppose that G has no isolated vertices. Select a vertex u with x u = 0 and let {u, v} ∈ E. Then we have strict inequality in (14) and so A α (G) is positive definite. ✷…”
Section: Positive Semidefinitness Of a Amentioning
confidence: 99%
“…was intensively studied for several cases. In [1], de Freitas et al studied the case for graphs with no cycles of length 4 and 5, and two conjectures are formulated for the maximum q 1 (G) of even/odd cycle-free graphs.…”
Section: Even/odd Cycle-free Graphsmentioning
confidence: 99%
“…Before going further, we shall make three remarks. First, recall an estimate of q S + n,k given in [7], where it was shown that if k ≥ 2 and n > 5k 2 , then…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…Also, let S + n,k be the graph obtained by adding an edge to S n,k . In [7] the following conjecture has been raised:…”
Section: Introductionmentioning
confidence: 99%